Cloud-top entrainment analyzed with a Lagrangian parcel tracking model in large-eddy simulations - Yamaguchi, Takanobu, author; Randall, David A. (David Allan), 1948-, advisor; Beveridge, J. Ross, 1957-, committee member; Denning, A. Scott, committee member; Krueger, Steven K., committee member; Schubert, Wayne H., committee member (Colorado State University. Libraries, 2010)
Despite decades of research, cloud-top entrainment has not been described with firm evidence. This leads to insufficient understanding of the physics of marine stratocumulus clouds. A Lagrangian Parcel Tracking Model (LPTM) was implemented in a large-eddy simulation model for detailed and direct analysis of the entrained air parcel following the parcel trajectory. The scalar advection scheme of the host model was replaced by a monotonic multidimensional odd-order conservative advection scheme. Tests with an idealized scalar field and stratocumulus turbulence suggested that the fifth-order scheme is optimal. Evaluation of the LPTM was performed with stratocumulus simulations. Parcel statistics agreed with Eulerian statistics, and the parcel paths agreed with the theoretical parcel paths. The Lagrangian budget equation for a scalar, however, generally does not hold for a simulated turbulence field, since the fractal nature of turbulence may cause numerical errors. Two large-eddy simulations were performed with grid spacing of O (5 m). The power spectra of these runs showed relatively good agreement with the energy cascade slope. A comparison with low-resolution simulations suggested that horizontal refinement is necessary for better representation of entrainment and microphysical processes. The LPTM with the high-resolution stratocumulus simulation showed that the location of entrainment is in cloud holes, which are drier downdraft regions. Parcels in the inversion layer, subsiding from the free atmosphere, are entrained in to the mixed layer. They are cooled and moistened by radiation, evaporation, and mixing. A mixing fraction analysis shows that the coolings during entrainment due to radiation and evaporation are comparable. The largest contribution to buoyancy reduction is the cooling due to mixing, for our simulation. The analysis also shows that buoyancy reversal occurs for the entrained parcels. Radiative cooling and cloud-top entrainment instability (CTEI) interact such that the radiative cooling forces larger saturation mixing fractions while CTEI forces smaller values. Additional simulations suggest that radiative cooling produces a negative feedback on the entrainment rate, which is strong enough to control turbulence and hide CTEI. Under such conditions, cloud breakup due to CTEI is unlikely.
Keywords: stratocumulus cloud; large eddy simulation; Lagrangian parcel tracking; entrainment; cloud-top entrainment instability; buoyancy reversal; Atmospheric turbulence; Cloud physics; Boundary layer (Meteorology); Turbulence